INDEX - Anand, Havelin; Anderson, Sandy; Borovoy, Alan; Brennan, Mary-Lu; Deschatelets, Gilles H.; Dowling, Patrick J.; Drover, Ellis R.; Feeley, James; Flower, Maurene; Foster, Anne; Gibson, Bob; Glover, D. W.; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF